Facing Aids : the challenge, the churches' response: A WCC study documents. (Switzerland : WCC Publications, 1997)
Includes bibliographical references
Notes: The study document is the result of a meeting of the central committee of the World Council of Churches in Johannesburg, South Africa in 1994
Keywords: AIDS (Disease) -- Religious aspects -- Christianity